Competitive anxiety or Coronavirus anxiety? The psychophysiological responses of professional football players after returning to competition during the COVID-19 pandemic - Mehrsafar, A. H.; Zadeh, A. M.; Sánchez, J. C. J.; Gazerani, P. (Psychoneuroendocrinology, 2021)
Objective: This study aimed to examine the relationship between competitive anxiety, fear/anxiety of COVID-19, and autonomic and endocrine stress responses in professional football players after returning to competition during the COVID-19 pandemic. Methods: Ninety male professional football players (age: 26.33 ± 2.48 yr) volunteered to participate in this study, which included an official competition. Psychophysiological responses, including the Fear of COVID-19 Scale, the Coronavirus Anxiety Scale, and the Competitive State Anxiety Inventory-2 Revised, were collected 30 min before the competition. In addition, salivary alpha-amylase (sAA) and salivary cortisol (sCort) were collected at 8 a.m. and 15 min before the competition. Results: The main findings, based on the Pearson correlation, showed significant positive correlations between COVID-19 anxiety and somatic competitive anxiety (p = 0.01), cognitive competitive anxiety (p = 0.01), and competition response of sCort and sAA (p = 0.01). Moreover, fear of COVID-19 was positively correlated with COVID-19 anxiety (p = 0.01). On the contrary, the awakening response of sCort and sAA was not found to be correlated with psychological parameters (all p > 0.05). The analysis also indicated that there was no significant correlation between self-confidence with other psychological and physiological variables (all p > 0.05). The regression analysis showed that cognitive anxiety was a relevant predictor for the competition response of sCort and sAA (p < 0.05). Moreover, COVID-19 anxiety was the only predictor of somatic and cognitive anxiety (p < 0.05). Conclusions: The present study provides the first preliminary evidence that COVID-19 anxiety and competitive anxiety might pose a negative impact on the athletic performance of professional football players during COVID-19 pandemic competitions. Thus, research is needed to build a strategy to reduce the psychophysiological stress related to COVID-19 and competition response.